Does carbon nanotube buckypaper affect mode-I and II interlaminar fracture toughness under quasi-static loading? - de Paula Santos, Luis Felipe [UNESP] (2023)
Carbon fiber reinforced polymer (CFRP) composites are widely used to produce structural components. However, their low interlaminar strength makes them susceptible to delamination, limiting structural applications. Aiming to solve this problem, this work proposes adding carbon nanotubes buckypaper (BP) into CFR thermoplastic composites as an interlayer to enhance the interlaminar strength through the BP bridging effect. Despite this objective, the carbon nanotube BP changed the delamination behavior in mode-I, creating an easy pathway for crack growth (smooth fracture surface) and reducing the interlaminar strength. An opposite behavior was observed for mode-II, in which BP acted as an obstacle for crack growth through the shear direction due BP bridging effect, which slightly improved interlaminar strength, resulting in a rougher surface. The experiments demonstrated through the energy involved in crack growth, the roughness of the fracture surface, and the amount of fracture mechanisms when BP was incorporated that in mode-I the delamination strength decreased, while it increased under the shear mode. This evidences that the BP bridging effect is influenced by the loading mode. Finally, this work highlights the need to study individual modes I and II in composites with buckypaper as an interlayer, since it influences the interlaminar toughness differently.